DAMPAK PERTUMBUHAN PENDUDUK TERHADAP KETAHANAN PANGAN (BERAS) KALIMANTAN BARAT - B01109057, MIS’ADAH (Jurnal Pembangunan dan Pemerataan, 2016)
This research analyzes the impact of population growth on food security with special emphasis on population’s food adequacy.  This research also estimates (projecting) the food need of population by year 2020 as well as analyzing the efforts have been done by local authority regarding food security matters from population aspects. This research applies qualitative descriptive method to analyze time series and literature data. Result of the research shows that population growth of West Kalimantan Province year 1995-2013 is at 1.27%. This implicated to the increase of food need to be 645.849 ton, while rice consumption decreased to be 106,35 kg/capita/year. Based on population projection, which is predicted to be 5.134.000 peoples by 2020, the rice need of West Kalimantan Province by the year is estimated at 817.937 ton. Meanwhile, rice supply will be around 1.248.301 ton.  On the other hand, Local Government of West Kalimantan Province has carried out some efforts on food security matters including that of through population growth control. This can be depicted from birth control program, in which improvement of quality of family planning program has resulted in the increase of new family planning by mix contraception reaches 153.743 acceptors. The other program is the prevention of early marriage by improvement of adolescent’s life. This program is conducted through personal counseling. For this purpose, there have been 228 counseling groups established, which means 102.2% from enacted target.  On production side, the efforts of Local Government of West Kalimantan Province for coping with food security problems were done by increasing rice production. By year 2013, rice production of the province was recorded at 1.441.876 ton. It increased 16.50% from previous year. The other effort was including the utilization of potential rice field areas, in which by year 2013 total rice field area has reached 310.102 ha. Key words: food adequacy (rice), rice supply, rice needs, rice consumption and government efforts.